Determinants of Knowledge Transfer in a Region - Justyna Zygmunt (Barometr Regionalny)
The main goal of the paper is to identify the determinants of knowledge transfer in a region on the basis of literature studies. The paper begins by discussion of the concept of knowledge transfer and its importance to regional development. Then it focuses on transfer of knowledge, with regard in particular to the triple-helix model. It also indicates the concept of success in the processes of knowledge transfer. A section of the paper contains a discussion of the determinants of transfer of knowledge in a region. The basis for recognition of the determinants in question were literature studies. On these grounds evidences were found to suggest that knowledge transfer in a region is determined by heterogeneous factors. The findings provide the basis for developing practical advice on effective knowledge transfer practices.